Facilitators and Barriers to Person‐centred Care in Child and Young People Mental Health Services: A Systematic Review. (2nd December 2016) - Gondek, Dawid; Edbrooke‐Childs, Julian; Velikonja, Tjasa; Chapman, Louise; Saunders, Felicity; Hayes, Daniel; Wolpert, Miranda
Abstract : Implementation of person‐centred care has been widely advocated across various health settings and patient populations, including recent policy for child and family services. Nonetheless, evidence suggests that service users are rarely involved in decision‐making, whilst their preferences and goals may be often unheard. The aim of the present research was to systematically review factors influencing person‐centred care in mental health services for children, young people and families examining perspectives from professionals, service users and carers. This was conducted according to best practice guidelines, and seven academic databases were searched. Overall, 23 qualitative studies were included. Findings from the narrative synthesis of the facilitators and barriers are discussed in light of a recently published systematic review examining person‐centred care in mental health services for adults. Facilitators and barriers were broadly similar across both settings. Training professionals in person‐centred care, supporting them to use it flexibly to meet the unique needs of service users whilst also being responsive to times when it may be less appropriate and improving both the quantity and quality of information for service users and carers are key recommendations to facilitate person‐centred care in mental health services with children, young people and families. Copyright © 2016 John Wiley & Sons, Ltd. Key Practitioners Messages: As research shows, children and young people are rarely actively involved in their treatment within mental health services. This is despite a strong recent emphasis on providing care within child and young people mental health services according to person‐centred principles. Still, there is little known about factors affecting provision of person‐centred care with this population. As found by the current study, the most commonly reported factors affecting provision of person‐centred care were information sharing (in an appropriate amount and at a right time), listening, respecting and validating, quality of relationship and support, capacity of children and young people to be involved in their care, parental involvement and shortage of resources. These factors were cited as both facilitators and barriers and were found to be universally important by service users, their carers and professional working at the services. The key factors were broadly similar to those reported among adults, particularly regarding information sharing/communication, capacity of service users to be involved and available resources. The main difference was related to a more complex role of a carer in children/young people services. The key recommendations of the review to improve provision of person‐centred care are providing professionals with more training in using the approach, supporting them to use it flexibly to meet the unique needs of service users whilst also being responsive to times when it may be less appropriate and improving both the quantity and quality of information for service users.